Direct bridging to cardiac transplantation with the surgically implanted Impella 5.0 device. Issue 3 (27th February 2020) - Seese, Laura; Hickey, Gavin; Keebler, Mary E.; Mathier, Michael A.; Sultan, Ibrahim; Gleason, Thomas G.; Toma, Catalin; Kilic, Arman
Abstract: This study evaluated outcomes of direct bridging to orthotopic heart transplantation (OHT) with the Impella 5.0 device. Adult recipients in the United Network for Organ Sharing registry bridged to OHT with the Impella 5.0 device between 2010 to 2018 were included. Outcomes included waitlist and post‐transplant survival. A total of 236 patients were wait‐listed with Impella 5.0 support, and 24% (n = 57) underwent bridge to OHT. Early and late post‐transplant survival was excellent at 96.5% at 30 day, 93.8% at 90‐day, and 90.3% at 1‐year follow‐up. Post‐transplant complications were infrequent, but the most common were renal failure requiring dialysis (8.8%, n = 5), cerebrovascular accidents (1.8%, n = 1), and pacemaker implant (1.8%, n = 1). The rate of waitlist removal for death or clinical deterioration was 20.0% (n = 47); however, the majority of patients were bridged to OHT (24%, n = 57) or durable continuous‐flow left ventricular assist device (37.0%, n = 87). The median time supported on the device, while waitlisted was 13 days (Interquartile range [IQR] 7, 20 days). The Impella 5.0 device can be used as a direct bridge to OHT with excellent survival and minimal post‐transplant morbidity. Overall, these data support the utilization of Impella 5.0 as a bridge to OHT in select patients with refractory cardiogenic shock.